J.J. Pizzuto's fabric science - Johnson, Ingrid, 1951-; Cohen, Allen C., (Writer on textile industry), ....-; Sarkar, Ajoy K., ....-; Pizzuto, Joseph J. (Joseph James), ....- (New York : Fairchild Books, 2015)
With an increased emphasis on the global industry of textiles, the best-selling Fabric Science, 11th Edition provides the most comprehensive and current introduction to textiles-from fibers through finished fabrics. The eleventh edition has been fully updated to reflect the current industry and applications to fashion, home goods, interior design, and related industries.
Previous edition: 2012.
Keywords: Textile fabrics; Textile industry